[PP.30.08] THE ECONOMICS OF OBESITY: FOOD PRICE POLICIES IMPROVE DIET QUALITY WHILE INCREASING SOCIOECONOMIC INEQUALITIES IN NUTRITION. (September 2016) - De Rosa, M.; Mancini, A.; Lombardi, A.; Cerini, L.; Leosco, D.; Ferrara, N.
Abstract : Objective: Observed links between obesity and socioeconomic position may be related to dietary energy(DE) density (ED) and energy cost(EC). An inverse relationship between ED of foods (F) and their EC means that more DE are associated with lower daily F consumption costs and may be effective saving money. Design and method: Experimental economics was used to examine 2 price (P)manipulations: a) a fruit and vegetable P subsidy named "fruit and vegetables condition"; b) a healthy-product subsidy coupled with an unhealthy-product tax named "nutrient profile condition". We used SAIN, LIM, nutrient profiling system, which classifies each individual F according to its overall nutritional quality which then allows for a F item to be taxed or subsidized. Women (W) from low (N = 85) and medium-incomes (N = 43) selected a daily F basket, first, at current P and then at manipulated P. Redistributive effects of experimental conditions were assessed by comparing the extent of savings induced by subsidies and of costs generated by the tax on the 2 income groups. ED (kcal/100 g), free sugars (%E) and the mean adequacy ratio (MAR) were used as nutritional quality indicators. Results: DE was independently and significantly associated with higher BMI in W (β = 0.45 (95% CI 0.13–0.83)) and trended toward a significant association in men (β = 0.38 (- 0.008 to 0.64), P = 0.054). DE was associated with higher waist circumference in W (β = 1.21 (0.32–1.90)) and men (β = 1.42 (0.56–2.10)). DE was also independently associated with elevated fasting insulin (β = 0.67 (0.19 - 1.22)) and the metabolic syndrome (prevalence ratio = 1.12 (95% CI 1.04–1.18)). Conclusions: F P policies may improve diet quality while increasing socio-economic inequalities in nutrition. Epidemiologic analyses suggest that the low-cost DE also tend to be nutrient poor. Limiting access to inexpensive F through taxes on frowned upon fats and sweets is a regressive measure. The broader problem may lie with growing disparities in incomes and wealth, declining value of the minimum wage, F imports, tariffs, and trade. Obesity in the world is a largely economic issue.